2008
DOI: 10.1080/15226510701827077
|View full text |Cite
|
Sign up to set email alerts
|

Phytoextraction of Zinc, Copper, Nickel and Lead from a Contaminated Soil by Different Species ofBrassica

Abstract: In a pot culture experiment, five different species of Brassica (Brassica juncea, Brassica campestris, Brassica carinata, Brassica napus, and Brassica nigra) were grown for screening possible accumulators of heavy metals, viz. Zn, Cu, Ni, and Pb. The plants were grown to maturity in a soil irrigated with sewage effluents for more than two decades in West Delhi, India. The soil analysis showed enhanced accumulation of Zn, Cu, Ni, and Pb in this sewage-irrigated soil. Among all species, B. carinata showed the hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(21 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…Indian mustard ( Brassica juncea L.) being the hyperaccumulator of metal(oids) can accumulate a high concentration of Cu and translocate much into above-ground parts that can be detrimental to any plant growth. Thus, maintaining Cu-homeostasis is essential for a plant to survive under high Cu, either through vacuolar sequestration, storage, or transport of metal ions from the cytoplasm to outer compartments [ 8 , 9 , 10 ]. This ability of B. juncea makes it a suitable model plant material to study the impact of high Cu concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Indian mustard ( Brassica juncea L.) being the hyperaccumulator of metal(oids) can accumulate a high concentration of Cu and translocate much into above-ground parts that can be detrimental to any plant growth. Thus, maintaining Cu-homeostasis is essential for a plant to survive under high Cu, either through vacuolar sequestration, storage, or transport of metal ions from the cytoplasm to outer compartments [ 8 , 9 , 10 ]. This ability of B. juncea makes it a suitable model plant material to study the impact of high Cu concentration.…”
Section: Introductionmentioning
confidence: 99%
“…B. alba were less than Brassica napus in the production of large biomass of shoot as well as having a high concentration of copper in shoots and roots. Previously reported that B. juncea shows good accumulation of several heavy metals, including copper [27] [28]. Fargasova reported that B. alba have the ability to accumulate many heavy metals, including copper in the root and in greater numbers than in the shoot of plants [29].…”
Section: Discussionmentioning
confidence: 99%
“…At harvest, the concentration of Cu in the control plants was 16.5 mg kg -1 dry weight in the shoots and 220.6 mg kg -1 dry weight in the roots, which is in good agreement with the results of experiments on copper uptake by B. napus when no amendments were applied. 26,27 These results indicate that Cu uptake and translocation from roots to shoots was limited in the absence of amendments.…”
Section: Introductionmentioning
confidence: 88%